Humoral response to two doses of BNT162b2 vaccination in people with HIV. (16th December 2021) - Heftdal, Line Dam; Knudsen, Andreas Dehlbæk; Hamm, Sebastian Rask; Hansen, Cecilie Bo; Møller, Dina Leth; Pries‐Heje, Mia; Fogh, Kamille; Hasselbalch, Rasmus Bo; Jarlhelt, Ida; Pérez‐Alós, Laura; Hilsted, Linda Maria; Ostrowski, Sisse Rye; et al.
Abstract: Background: People with HIV (PWH) are at increased risk of severe COVID‐19. We aimed to determine humoral responses in PWH and controls who received two doses of BNT162b2. Methods: In 269 PWH and 538 age‐matched controls, we measured IgG and neutralizing antibodies specific for the receptor‐binding domain of SARS‐CoV‐2 at baseline, 3 weeks and 2 months after the first dose of BNT162b2. Results: IgG antibodies increased from baseline to 3 weeks and from 3 weeks to 2 months in both groups, but the concentrations of IgG antibodies were lower in PWH than that in controls at 3 weeks and 2 months ( p = 0.025 and <0.001), respectively. The IgG titres in PWH with a humoral response at 2 months were 77.9% (95% confidence interval [62.5%–97.0%], age‐ and sex‐adjusted p = 0.027) of controls. Conclusions: Reduced IgG antibody response to vaccination with BNT162b2 was found in PWH, and thus increased awareness of breakthrough infections in PWH is needed.